Preparation of activated carbon using sea mango (Cerbera odollam) with microwave-assisted technique for the removal of methyl orange from textile wastewater - Azmi, N.H.; Ali, U.F.M.; Muhammad Ridwan, F.; Isa, K.M.; Zulkurnai, N.Z.; Aroua, M.K. (Taylor & Francis, 2016)
Sea mango (Cerbera odollam), a non-edible fruit which is abundantly available in Malaysia was transformed into a potential low-cost activated carbon for the removal of methyl orange (MO) (mono azo dye) from textile wastewater. The activated carbon was subjected to carbonization process at 200°C with nitrogen (N2), followed by chemical activation with phosphoric acid (H3PO4) and physical activation using microwaves at 500°C for 2 h. The Brunauer–Emmet and Teller surface area for the produced activated carbon was 1,437 m2/g. The effects of several operating parameters, such as activated carbon dosage, contact time; initial concentration, and pH at room temperature on the adsorption process of MO from simulated textile wastewater were evaluated. The minimum duration for the dye adsorption reached the equilibrium state was 60 min. Removal of dye in acidic solutions was preferred rather than in basic solution. Higher initial dye concentration performed better on dye removal than lower concentration. Adsorption behavior of MO on sea mango activated carbon was expressed by both Langmuir and Freundlich isotherms.